A new approach for quantification of corrosion losses on steels exposed to an artificial seawater environment - Abbas, Muntazir; Simms, Nigel J.; Rizvi, Syed Haider Mehdi (Taylor & Francis, 2023)
The selection methodology for thickness loss measurement is very important to determine the extent of corrosion damage, as well as in formulation of corrosion prediction models and inspection/maintenance plans for offshore structures. This paper introduces a more accurate corrosion measurement technique, based on the pre-exposure dimensional metrology and post-exposure optical microscopy/image analysis on the cross-sections of steel samples. During this corrosion test, the surface grinded and uncoated steel samples were submerged vertically in an artificial seawater solution, for a duration of up to a maximum of 365 days. The corrosion damage experienced on the steel samples means that the dimensional metrology can be more accurate, and useful approach to measure both uniform and localised corrosion losses simultaneously than the conventional average mass loss method.
Keywords: artificial seawater; corrosion loss measurements; dimensional metrology; image analyser; uniform/localised corrosion